Circulating Galectin-3 Evaluation in Dogs With Cardiac and Non-cardiac Diseases - Lee, Ga-Won; Kang, Min-Hee; Ro, Woong-Bin; Song, Doo-Won; Park, Hee-Myung (Frontiers in Veterinary Science, 2021)
Galectin-3 is involved in important biological functions such as fibrogenesis and inflammation. Notably, it is associated with various diseases and plays a major role in cardiac inflammation and fibrosis. Although heart diseases are relatively common in dogs, few studies have analyzed the circulating galectin-3 concentration in dogs with various heart diseases, including myxomatous mitral valve disease, patent ductus arteriosus, and pulmonic stenosis. The aims of the present study were to evaluate the effect of heart disease on circulating galectin-3 levels in dogs, and also to evaluate the correlation between galectin-3 concentration and conventional echocardiographic indices along with N-terminal pro-B-type natriuretic peptide (NT-proBNP) concentration in dogs with heart diseases. The medical records and archived serum samples of 107 dogs were evaluated retrospectively. In total, 107 dogs were classified into healthy dogs (n = 8), cardiac disease (n = 26), and non-cardiac disease groups (n = 73). The circulatory galectin-3 levels were analyzed using a commercially available canine-specific galectin-3 enzyme-linked immunosorbent assay kit. This study demonstrated that dogs with heart, endocrine, and dermatologic diseases had significantly higher galectin-3 levels than healthy dogs (p = 0.009, p = 0.007, and p = 0.026, respectively). Among dogs with heart diseases, dogs with concentric cardiomyopathy had significantly increased circulatory galectin-3 levels compared to healthy dogs (p = 0.028). E’/A’ had a positive association with galectin-3 levels among conventional echocardiographic indices. Moreover, the galectin-3 concentration could predict diastolic dysfunction. In dogs with myxomatous mitral valve disease, a significantly positive correlation was revealed between galectin-3 levels and NT-proBNP levels (p = 0.007). Overall, this study demonstrates that circulatory galectin-3 levels increase in dogs with heart, endocrine, and dermatologic diseases. Moreover, this study demonstrates that galectin-3 concentration could be helpful to evaluate cardiac remodeling and diastolic function. Further large-scale research is required to evaluate the role of circulating galectin-3 in dogs with heart diseases.